Pelatihan Daring Penulisan Artikel Ilmiah Bagi Guru Sekolah Menengah Kejuruan Negeri 1 Sidoarjo - Fitria Nur Hasanah; Fika Megawati; Noly Shofiyah; Miftahul Jannah; Rindiani Rindiani (Jurnal Pemberdayaan Masyarakat, 2020)
As a professional teacher must have various abilities, one of the ability to write scientific papers in the form of scientific articles. By writing scientific papers, in addition to getting a promotion, position and class, will be used as a benchmark of success and to demonstrate professionalism. Departing from the problems at the partner school, the purpose of this training activity is to improve teachers' understanding and ability to write scientific articles that are in accordance with the journal template. The target of this activity is teachers at SMK N 1 Sidoarjo. The methods used in this training are lecture, question and answer, mentoring to write scientific articles, and citing references. Based on the results of the pre-test and post-test conducted during the training showed that there was an increase in knowledge about writing scientific articles. Increasing the percentage of knowledge about the article component by 46%, increasing the ethical knowledge of writing articles by 58%, and increasing knowledge about uploading articles in national journals by 54%.